Pengaruh Rasio Keuangan Terhadap Harga Saham : Studi pada salah satu perusahaan Sektor Industri Konsumsi - Rima Nur Lutfitasari; Indri Ayu Tansar; Tri Ningsih (Center of Research, STIE Pasundan, Bandung, Indonesia., 2021)
This study intends to determine the effect of financial report ratios on stock prices. This study departs from the phenomenon of stock price fluctuations in the consumption industry sector. Departing from stock prices that continue to fluctuate, this study aims to determine the effect of financial ratios on stock prices in a consumer industry sector company. The research method used is quantitative research methods with multiple regression analysis techniques carried out at one of the IDX companies for the period 2012-2019. The results showed that there was an effect of financial ratios on stock prices.